Celiac disease and Down syndrome mortality: a nationwide cohort study. Issue 1 (December 2017) - Ludvigsson, Jonas; Lebwohl, Benjamin; Green, Peter; Chung, Wendy; Mårild, Karl
Abstract Background Individuals with Down syndrome (DS) have increased mortality and are also at increased risk of celiac disease (CD). It is unknown if CD influences mortality in DS. In this study we examined the risk of death in individuals with DS according to celiac status. Methods In this nationwide population-based cohort study, we first identified individuals with CD (diagnosed 1969–2008) through small intestinal biopsy report data showing villous atrophy (Marsh stage III) from Sweden's 28 pathology departments. Celiac individuals were then matched with up to five reference individuals from the general population. In these cohorts we identified individuals with DS using International Classification of Disease codes (ICD) registered in the Swedish Patient Register (includes inpatients and hospital-based outpatients), the Medical Birth Register, and the Register of Congenital Malformations. Of 29, 096 individuals with CD, 201 (0.7%) had DS compared to 124 of the 144, 522 reference individuals (0.09%). Data on mortality were obtained from the Swedish Cause of Death Registry. Hazard ratios (HRs) for death were calculated using Cox regression. Results During follow-up, there were seven deaths among individuals with DS and CD (7/201, 3.5%) as compared with 14 deaths among DS individuals without a record of CD (14/124, 11.3%). Adjusting for potential confounders, CD did not influence the risk of death in DS (HR = 1.36; 95%CI = 0.33–5.59). Cardiovascular death occurred in two individuals with CD and three individuals without CD, while death from malignancy occurred in one individual with CD and two individuals without CD. Conclusion While both DS and CD have been linked to increased risk of death, this study found no excess mortality in DS patients with a concurrent diagnosis of CD, however confidence intervals were wide.